Effect of bempedoic acid on uric acid and gout in 3621 patients with hypercholesterolemia: pooled analyses from phase 3 trials. (25th November 2020) - Ray, K.K; Bakris, G.L; Banach, M; Catapano, A; Duell, P.B; Mancini, G.B.J; Bloedon, L; Feng, A; Gotto Jr, A.M
Abstract: Background: Bempedoic acid (BA), an oral ATP-citrate lyase inhibitor, significantly lowers low-density lipoprotein cholesterol levels in patients with hypercholesterolemia. In clinical trials of BA, small mean increases in uric acid have been reported. BA weakly inhibits organic anion transporter 2 (OAT2) in vitro, which may account for small elevations in serum uric acid. Purpose: To assess uric acid levels and incidence of gout with BA treatment. Methods: Data were pooled from 4 randomized (2:1), double-blind studies of BA (180 mg daily) vs placebo for 12 weeks to 52 weeks in patients with hypercholesterolemia on stable background lipid-lowering therapy. Safety assessments included adverse events of special interest (elevation in uric acid levels, gout) and laboratory assessments. Results: A total of 2424 patients treated with BA and 1197 patients on placebo were included in this analysis. Mean (SD) baseline uric acid levels were 6.0 (1.4) mg/dL for both groups. History of gout was reported by 5.2% (127/2424) and 5.8% (69/1197) in the BA and placebo groups, respectively. At week 12, mean (SD) serum uric acid levels (% change from baseline) increased from baseline with BA treatment by 0.82 (0.97) mg/dL (14.8%) vs –0.02 (0.82) mg/dL (0.67%) for placebo. Elevations in serum uric acid levels typically occurred within the first 4 weeks of treatment, remained stable during treatment, and returned to baseline after treatment discontinuation. Gout was reported in 1.4% (BA) and 0.4% (placebo) of patients, and hyperuricemia was reported in 1.7% (BA) and 0.6% (placebo) of patients. Other potential clinical consequences of elevated uric acid levels (eg, events associated with nephrolithiasis), were similar between groups (0.7% vs 0.8%). In both groups, patients who reported gout during the studies were more likely to have a medical history of gout or elevated baseline uric acid levels (Table). Few patients discontinued treatment due to gout (n=1, <0.1% [BA]) or uric acid increases (n=2, <0.1% [BA]). Conclusion: Mean increases in uric acid levels were small, remained stable while patients continued to receive treatment, were infrequently associated with AEs, and were reversible on discontinuation of BA Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Esperion Therapeutics funded the research for this study and provided writing support for this abstract. Medical writing assistance was provided by Agnella Izzo Matic, PhD, CMPP, and Kelly M Cameron, PhD, CMPP, of JB Ashtin.